The Genome Sequence of Bifidobacterium moukalabense DSM 27321 Highlights the Close Phylogenetic Relatedness with the Bifidobacterium dentium Taxon - Lugli, Gabriele Andrea (American Society for Microbiology, 2014)
Bifidobacterium moukalabense DSM 27321 is the reference strain for a recently described new bifidobacterial species that has been isolated from a wild west lowland gorilla. Here, we report the whole-genome sequence of DSM 27321, which supports very close phylogenetic relatedness with members of the Bifidobacterium adolescentis phylogenetic group and, in particular, the Bifidobacterium dentium taxon.